Enhanced degradation of ibuprofen by heterogeneous electro-Fenton at circumneutral pH. (October 2018) - Liu, Dun; Zhang, Hao; Wei, Yuquan; Liu, Bo; Lin, Yipeng; Li, Guanghe; Zhang, Fang
Abstract: Fenton based reactions are effective for pharmaceutical removals, but traditional Fenton processes have drawbacks of pH adjustment and large amount of produced iron sludge. To overcome these challenges, a heterogeneous electro-Fenton process was proposed for effective contaminant degradation at circumneutral pH without iron sludge production. The anti-inflammatory drug ibuprofen (a common pharmaceutical in natural waters) was used as a representative contaminant. Activated carbon fibers (ACFs) supported ferric citrate (Cit-Fe/ACFs) was synthesized and used as the cathode, and RuO2 /Ti was used as the anode. H2 O2 was electro-generated in situ from O2 reduction and the production rate of OH per unit area was 6.8 μM W −1 cm −2 using Cit-Fe/ACFs cathode. A maximal ibuprofen degradation of 97% was obtained after 120 min at the current density of 7 mA cm −2 . The electrical energy per order ( E EO ) varied from 0.24 ± 0.03 to 2.65 ± 0.04 kWh log −1 m −3 when the current density ranged from 1 to 7 mA cm −2 . The Cit-Fe/ACFs cathode showed relatively good reusability and ∼85% IBP removal was achieved after 6 cycles of degradation. Our results showed that the prepared Cit-Fe/ACFs cathode was promising for the treatment of pharmaceutical contaminants. Graphical abstract: Image 1 Highlights: Effective removal of ibuprofen by heterogeneous electro-Fenton process. H2 O2 and OH were electro-generated on Cit-Fe/ACFs cathode. A maximal ibuprofen degradation of 97% was obtained at circumneutral pH. No iron sludge was produced during the treatment process.